In Vivo Evaluation of Painful Symptomatology after Endodontic Treatment Performed Using Two Different Irrigation Needle Insertion Depths - Tavares, Sarah Gutierrez; Fontana, Carlos Eduardo; Martin, Alexandre Sigrist De; Pinheiro, Sérgio Luiz; Pelegrine, Rina Andrea; Rocha, Daniel Guimarães Pedro (European Journal of Dentistry, 2020)
Objective The main purpose of this study was to evaluate pain symptoms in patients after endodontic treatment performed in a single session in teeth with vitality or pulp necrosis, comparing two depths of insertion of the NaviTip irrigation needle.Materials and Methods One-hundred upper uniradicular teeth were selected and divided into four groups (n = 25), namely Bio group 1 (live pulp/1 mm from the foramen), Bio group 3 (live pulp/3 mm from the foramen), Necro group 1 (pulp necrosis/1 mm from the foramen), and Necro group 3 (pulp necrosis/3 mm from the foramen). All canals were instrumented with Wave One Gold System. Irrigation was performed using 2.5% NaOCl. The teeth were filled using the single-cone technique with AH Plus sealer using a McSpadden compactor. After treatment, patients answered a questionnaire with a visual analog scale scored from 0 to 10 at 1, 3, and 7 days after treatment.Statistical Analysis Data were analyzed using Mann–Whitney U, Wilcoxon, and Friedman tests.Results There was a decrease in average pain levels at the three time points for both vital and necrotic teeth (p < 0.05). There were no significant differences in postoperative pain levels comparing needle depth, or vitality and pulp necrosis (p > 0.05). The percentage of mild pain increased over time and moderate pain decreased, regardless of pulp condition. There was no incidence of acute pain at any time.Conclusions Post-treatment endodontic pain levels in upper uniradicular teeth with or without pulp vitality resulted in similar pain scores, regardless of the depth of insertion of the irrigation needle in relation to the apical foramen.
Keywords: postoperative pain; insertion; needle; irrigation; single session